Meat inspection and control in the slaughterhouse - Ninios, Thimjos; Lundén, Janne; Korkeala, Hannu (Hannu J.); Fredriksson-Ahomaa, M. (Maria) (John Wiley & Sons Inc., 2014)
Meat inspection, meat hygiene and official control tasks in the slaughterhouse have always been of major importance in the meat industry, and are intimately related with animal diseases and animal welfare. The history of meat inspection has largely been a success story. Huge steps have been taken over more than a century to prevent the transmission of pathogenic organisms and contagious diseases.